2015
DOI: 10.21083/ajote.v4i1.2804
|View full text |Cite
|
Sign up to set email alerts
|

Usability of Computers in Teaching and Learning at Tertiary-Level Institutions in Uganda

Abstract: Since a computer-enriched learning environment is positively correlated with users' attitudes towards computers in general, the rationale of this study was to investigate the extent to which computers were applied in the teaching and learning at tertiary-level institutions; specifically at the Core Primary Teachers' Colleges (PTCs). The study accordingly set out to examine this duofold ideal at Shimoni and Kibuli Core PTCs; both in Kampala District in Uganda. The specific objectives were to find out the level … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…For nearly a decade, research [4]- [7] in Uganda consistently demonstrated a disparity between classroom educational technology and individuals' competency in utilising these technologies within education programs. These studies indicate that digital technology is underutilised in Uganda's education programs, and many people lack the necessary digital skills to effectively employ available digital resources as instructional or learning tools [8].…”
Section: Introductionmentioning
confidence: 99%
“…For nearly a decade, research [4]- [7] in Uganda consistently demonstrated a disparity between classroom educational technology and individuals' competency in utilising these technologies within education programs. These studies indicate that digital technology is underutilised in Uganda's education programs, and many people lack the necessary digital skills to effectively employ available digital resources as instructional or learning tools [8].…”
Section: Introductionmentioning
confidence: 99%